Application of A Video And Image Watermarking Based On Histogram Shape - Afeef, P; Muhammed, Ihsana (International Journal of Computer Sciences and Engineering, 2025)
Digital watermarking is a powerfull tool to protect digital multimedia content from illegal distribution and unatherised acces.Thus it can be used in multimedia applications for videos and images.Here we are proposing a new watermarking scheme which is Histogram based and it can be used to provide high security, robustness.This watermarking is aimed for images and videos also. The shape of histogram of image is manipulated to for the efficient insertion of digital watermarks to the images.The movement of pixels from one region to other will remove the side effect of Gaussian filtering. The proposed system is highly robust as it makes changes to the histogram of the image. The use of secret key improves the security of the proposed system. Also the imperceptiblity of watermarking makes the scheme perfect.Here the three step scenario for watermarking makes a good protection system for digital contents.In video watermarking the video frames are seperated before inserting the watermarks.The digital watermarking can be used in applications like identifying content owners, Protection of video contents,filtering of digital contents,ownership communication,..etc